Lexical interference in teaching English to Lithuanians - Šurnaitė, A. (Psichologija, 1977)
Lexical interference manifests itself in words which are similar in their form in both languages but differ in meaning, in words which are different in form and do not coincide in all their meanings and in those words which differ in their grammatical distribution. Lexical interference in the latter cases is covert and produces an illusion that learners have not mastered the English morphology or syntax. Such words need a specially designed programme and carefully selected ways of presenting and practising them.
Keywords: lexical interference; teaching English